Вы находитесь на странице: 1из 13

IIT – ian’s

P

A

C

E

216 - 217 ,2nd floor , Shopper’s point , S. V. Road. Andheri (West) Mumbai – 400058 . Tel: 26245223 / 09

Practice Question

LEVEL –1

Differential Equation

Question

based on

Order and Degree of Differential Equation Q.1

Q.2

Q.3

Q.4

Q.5

A differential equation of first order and first degree is-

(A)

x

dy

dx

2

– x + a = 0

(C) dy + dx = 0

(B)

d

2

dx

y + xy = 0

2

(D) None of these

The order and degree of differential equation

dx + y  2
1  x

dy = 0 are respectively-

 (A) 1, 2 (B) 1, 1 (C) 2, 1 (D) 2, 2

The order and degree of the differential equation

y =

(A)

(C) 2
dy +
a 2  dy 
2
x
 b
is-
dx
dx
1, 2
(B) 2, 1
1, 1
(D) 2, 2

The order and degree of the differential equation

4

dy

dx

2

2/3

=

d

2

dx

y are-

2

 (A) 2, 2 (B) 3, 3 (C) 2, 3 (D) 3, 2

The order and the degree of differential equation

4

d

y

dx

4

3

4

d

y +

3

dx

respectively-

8

d

2

y

dx

2

dy +

8 dx

4y

=

0

are

 (A) 4, 1 (B) 1, 4 (C) 1, 1 (D) None of these

Q.6

The order and degree of differential equation

(xy 2 + x) dx + (y – x 2 y) dy = 0 are-

 (A) 1, 2 (B) 2, 1 (C) 1, 1 (D) 2, 2 Q.7
The
degree
of
the
differential
equation
3
2
d
y
 dy 
+
1 
 = 0 is
-
2
dx
dx
(A) 1
(B) 2
(C) 3
(D) 6

Q.8

The order of the differential equation whose

solution is y = a cos x + b sin x + ce x is-

 (A) 3 (B) 2 (C) 1 (D) None of these

Q.9

The differential equation of all circles of radius a is of order-

 (A) 2 (B) 3 (C) 4 (D) None of these

Q.10

Q.11

Q.12

The order of the differential equation of all circles

of radius r, having centre on y-axis and passing through the origin is-

(A)

1

(B) 2

(C) 3

(D) 4

The

degree

d

2

dx

(A)

(C)

y + 3

2

1

3

dy

dx

2

of

the

= x 2 log

differential

d

2

y

dx

2

is-

(B) 2 (D) None of these

The differential equation

x

d

2

y

dx

2

2

+

dy

dx

4

+ y = x 2 is of -

 (A) degree 2 and order 2 (B) degree 1 and order 1 (C) degree 4 and order 3 (D) degree 4 and order 4

equation

IIT - ian’s PACE ; ANDHERI / DADAR / CHEMBUR / THANE ; Tel : 26245223 / 09 ; .www.iitianspace.com 1

Question

based on

Linear and Non-linear Differential Equation Q.13

Q.14

Q.15

Which of the following equation is linear?

(A)

dy + xy 2 = 1 dx

(B) x 2 dx dy

+ y = e x

(C)

(D)

dy + 3y = xy 2 dx

x

dy + y 2 = sin x dx

Which of the following equation is non- linear-

(A)

dy = cos x dx

(C) dx + dy = 0

(B)

d

2

y

dx

2

+ y = 0

dy +

3 = y 2

(D) x dx

dy / dx

Which of the following equation is linear ? 2
2
2
d
y
 dy 
(A)  
+ x 2
2
dx
dx
= 0
 
   
2
dy
 dy 
(B)
y =
+
1  
dx
dx
dy +
(C)
dx
y = log x
x
(D)
dy – 4 = x
y dx
 Question Formation of Differential Equation based on

Q.16

Q.17

y

equation-

(A)

=

4

dx

sin

3x is a solution of the differential

dy – 8y = 0

(B) dx

(D)

d

2

dx

y – 9y = 0

2

dy + 8y = 0

dx

d

2

(C)

y + 9y = 0

2

The differential equation of the family of curves represented by the equation x 2 + y 2 = a 2 is-

(A)

dy

x + y dx

dy

(B) y dx

= x

= 0

(C)

y

d

2

y

dx

2

+

dy

dx

2

= 0

(D) None of these

Q.18

Q.19

Q.20

Q.21

The differential equation of the family of curves

y 2 = 4a (x + a), where a is an arbitrary constant,

is-

(A)

(B)

(C)

(D)

1

 

dy

dx

2

2

y

y

1

 

dy

dx

dy

dx y + 2 dx

d

2

2

= 2x dx dy

= 2x dx dy

= 0

dy

dx

3

dy + 3 dx

+ y = 0

The differential equation of all the non-vertical lines in the xy- plane is-

(A)

(C)

dy – x = 0 dx

d

y = 0

dx

2

2

(B)

(D)

d

dx y x dx

d

2

dy = 0

2

2

y

dx

2

+ x = 0

The differential equation of the family of curves

represented by the equation (x – a) 2 + y 2 = a 2 is-

dy + x 2 = y 2

(A) 2xy dx

dy + x 2 + y 2 = 0

(B) 2xy dx

(C)

dy + x 2 = y 2

xy dx

(D) None of these

The differential equation of all parabolas whose axes are parallel to y- axis is-

(A)

(C)

y = 0

dx

3

d

3

3

d

y +

dx

3

d

2

x

dy

2

= 0

(B)

(D)

x = c

dy

2

d

2

2

2

dy

dx y + 2 dx

d

= c

Q.22 The differential equation of family of curve

y = Ae x + Be x , where A and B are arbitrarily constants, is

d

2

y

(A)

(C) y

+ y = 0

dx

d

2

2

y

dx

2

dy

dx

2

= 0

(B)

d

2

dx

y = y

2

(D) None of these

 Q.23 The differential equation for the line y = mx + c is (where c is arbitrary constant)- (A) dy = m dx dy + m = 0 (B) dx (C) dy = 0 dx (D) None of these Q.24 The differential equation of the family of curves v

=

A + B, where A & B are arbitrary constants, is-

r

 (A) d 2 v + 1 dv = 0 dr 2 r dr (B) d 2 v – 2 dv = 0 dr 2 r dr (C) d 2 v + 2 dv = 0 dr 2 r dr (D) None of these Question Variable separable method based on Q.25 The general solution of the differential equation dy = dx x y 2 2 is- (A) x 3 – y 3 = c (B) x 3 + y 3 = c (C) x 2 + y 2 = c (D) x 2 – y 2 = c Q.26 The general solution of the equation (e y + 1) cos x dx + e y sin x dy = 0 is- (A) (e y + 1) cos x = c (B) (e y – 1) sin x = c (C) (e y + 1) sin x = c (D) None of these Q.27 The solution of the differential equation dy = sec 2 x dx is- (A) y = sec x tan x + c (B) y = 2 sec x + c 1 (C) y = tan x + c 2 (D) None of these Q.28 The solution of the differential equation (1 + x 2 ) dx dy = x is- (A) y = tan –1 x + c

(B)

(C)

(D)

y = – tan 1 x + c

y =

1

2

log e (1 + x 2 ) + c

1

y = – 2 log e (1 + x 2 ) + c

Q.29

Q.30

Q.31

Q.32

Q.33

dy = e x (sin x + cos x) is-

The solution of dx

(A) y =

(B) y = e x (cos x – sin x) + c

e x (sin x – cos x) + c

(C)

(D)

y = e x sin x + c

y = e x cos x + c

dy = x log x is-

The solution of dx

(A) y = x 2 log x –

x 2

2

+ c

(B) y =

(C) y =

x 2

2

log x – x 2 + c

1

2 x 2 + 2

1

x 2 log x + c

(D) None of these

The solution of the differential equation

dy = (1 + x) (1 + y 2 ) is-

dx

 (A) y = tan (x 2 + x + c) (B) y = tan (2x 2 + x + c) (C) y = tan (x 2 – x + c)

 

 

x 2

2

 

 

the

x c

of

(D) y = tan

The

dy

x sec y dx

solution

= 1 is-

differential

 (A) x sec y tan y = c (B) cx = sec y + tan y (C) cy = sec x tan x (D) cy = sec x + tan x

equation

The solution of the equation 2
dy +
1
 y
= 0 is-
2
dx 1
 x
2
2
(A) x
1 y
– y
1 x
=
c
2
2
(B)
x
1 y
+ y
1 x
= c
2
2
(C)
x
1 y
+ y
1 x
=
c
(D)
None of these

Q.34

Q.35

Q.36

Q.37

Q.38

Solution of the equation

dy = – sin x sin y is-

cos x cos y dx

 (A) sin y + cos x = c (B) sin y – cos x = c (C) sin y. cos x = c (D) sin y = c cos x The general solution of the equation

d

2

y = –

dx

2

1

x

2

is-

(A) y = log x + c 1 x + c 2

(B)

y = – log x + c 1 x + c 2

1 + c 1 x + c 2

(C)

(D) None of these

y = – x

The general solution of the differential equation

e y dx dy + (e y + 1) cot x = 0 is-

 (A) (e y + 1) cos x = K (B) (e y + 1) cosec x = K (C) (e y + 1) sin x = K (D) None of these

The solution of the equation

dy = e xy + x 2 e y is-

dx

(A)

(C)

e y = e x +

x 3

3

+ c

e y = e x + x 3 + c

(B) e y = e x + 2x + c

(D) None of these

The

solution

of

the

differential

dy = e x + cos x + x + tan x is-

 dx (A) y = e x + sin x + (B) y = e x + sin x + (C) y = e x – sin x + (D) y = e x – sin x +

2

x

2

2

x

2

2

x

2

2

x

2

+ log cos x + c

+ log sec x + c

+ log cos x + c

+ log sec x + c

equation

Q.39

Q.40

Q.41

Q.42

Q.43

Q.44

The

(1 + cos x) dy = (1 – cos x) dx is-

solution

of

the

differential x
(A)
y = 2 tan
– x + c
2
(B)
y = 2 tan x + x + c
x
(C)
y = 2 tan
+ x + c
2
x
(D)
y = x – 2 tan
+ c
2
dy +
1
= 0, then-
If dx
2
1
 x
(A)
y + sin –1 x = c
(B)
y 2 + 2sin –1 x + c = 0
(C)
x + sin –1 y = 0
(D)
x 2 + 2 sin –1 y = 1

equation

differential

sec 2 x tan y dx + sec 2 y tan x dy = 0 is-

(A)

(C)

The

solution

of

the

equation

tan x = c tan y tan x = c cot y

(B) tan x = c tan (x + y)

(D) tan x sec y = c

 dy = The solution of dx 3e 2x  3e 4x e x  e  x
 (A) y = e 3x + c (B) –y = e 3x – c (C) y = – e 3x + c (D) None of these

is-

The general solution of differential equation

(4 + 5 sin x)

dy = cos x is-

dx

 1 (A) y = 5 log |4 + 5 sin x| + c (B) y = 1 5 log |4 + 5 cos x| + c (C) 1 y = – 5 log |4 – 5 sec x| + c (D) None of these The general solution of differential equation dy = log x is - dx (A) y = x (log x + 1) + c (B) y + x (log x + 1) = c (C) y = x (log x – 1) + c (D) None of these

Q.45

Q.46

Q.47

Q.48

Q.49

The

general

solution

of

differential

dy = sin 3 x cos 2 x + x e x

dx

is-

equation

(A) y =

1

5 cos 5 x +

1

3 cosec 3 x + (x + 1) e x + c

(B) y =

1

5 cos 5 x –

1

3 cos 3 x + (x – 1) e x + c

1

(C) y = – 5 cos 5 x –

(D) None of these

1

3 cos 3 x – (x – 1) e x – c

 The solution of the differential equation x(e 2y – 1) dy + (x 2 – 1) e y dx = 0 is- x 2 (A) e y + e –y = log x – + c 2 2 (B) x e y – e –y = log x – + c 2 2 (C) x e y + e –y = log x + + c 2 (D) None of these The solution of the differential equation

(1 + x 2 ) (1+ y) dy + (1 + x) (1+ y 2 ) dx = 0 is-

(A)

+ log (1 + y 2 ) = c

tan 1 x + log (1 + x 2 ) + tan 1 y

(B) tan 1 x –

1

2 log (1 + x 2 )

1

+ tan 1 y – 2 log (1 + y 2 ) = c

(C)

tan 1 x +

1

2

log (1 + x 2 ) + tan 1 y

+

1 log (1 + y 2 ) = c

2

(D) None of these

 The solution of the differential equation y dx – x dy = 0 is- (A) x = cy (B) xy = c (C) x = c log x (D) None of these The solution of differential equation

dy + y = y 2 is-

x dx

 (A) y = 1 + cxy (B) y = log (cxy) (C) y + 1 = cxy (D) y = c + xy

Q.50

Q.51

Q.52

Q.53

Q.54

Q.55

The

solution

of

the

differential

dy = e y cos x, given that y (0) = 0 is–

dx

 (A) e y = sin x + 1 (B) e y = cosec x + 1 (C) e y = cos x + 1 (D) e y = – sin x – 1 The solution of the differential

dy = x (1 + y 2 ) is-

(1 + x 2 ) dx

equation

equation

 (A) 2 tan –1 y = log (1 + x 2 ) + c (B) tan –1 y = log (1 + x 2 ) + c (C) 2 tan –1 y + log (1 + x 2 ) + c (D) None of these

Solution of the equation

(e x + 1) y dy = (y + 1) e x dx is-

 (A) c (y + 1) (e x + 1) + e y = 0 (B) c (y + 1) (e x – 1) + e y = 0 (C) c (y + 1) (e x – 1) – e y = 0

(D) c (y + 1) (e x + 1) = e y

The solution of the given differential equation

dy + 2xy = y is-

dx

(A) y =

ce

x

x

2

(B) y =

ce

x

2

x

 (C) y = ce x (D) y = ce  x 2 The solution of 2 d dx y = sec 2 x + xe x is- 2 (A) y = log (sec x) + (x – 2) e x + c 1 x + c 2 (B) y = log (sec x) + (x + 2) e x + c 1 x + c 2 (C) y = log (sec x) – (x + 2) e x + c 1 x + c 2 (D) None of these

The equation of the curve which passes through

the point (1, 1) & whose slope is given by

 (A) y = x 2 (B) x 2 – y 2 = 0 (C) 2x 2 + y 2 = 3 (D) None of these

2y , is -

x

Q.56

Q.57

Q.58

Q.59

Equation of curve passing through (3, 9) which satisfies the differential equation

dy = x +

dx

1

x

2

, is-

 (A) 6 xy = 3x 2 – 6x + 29 (B) 6 xy = 3x 3 – 29x + 6 (C) 6 xy = 3x 3 + 29 x – 6 (D) None of these

The equation of the curve through the point (1, 0)

 y  1 and whose slope is x 2  x (A) (y – 1) (x + 1) + 2x = 0 (B) 2x (y – 1) + x + 1 = 0 (C) x (y – 1) (x + 1) + 2 = 0 (D) None of these

is-

dy = e 2y and y = 0 when x = 5, the value of

(B) e 6 + 1

If dx

x for y = 3 is-

(A) e 5

(C)

e

6

9

2

(D) log e 6

The

differential

equation

dy +

y dx

(a is any constant) represents-

(A)

a

set

of

circles

having

y-axis

centre

x

=

on

a

the

(B) a set of circles centre on the x-axis

(C) a set of ellipses

(D) None of these

Question

based on

Differential Equation of the form dy/dx = f(ax + by + c) Q.60 dy = (x + y) 2 is- The solution of the equation dx (A) x + y + tan (x + c) = 0 (B) x – y + tan (x + c) = 0 (C) x + y – tan (x + c) = 0 (D) None of these Q.61 The solution of the differential equation

dy = cot 2 (x + y) is-

dx

 (A) y = x + 1/2 sin 2 (x + y) + c (B) y = x – 1/2 sin 2 (x + y) + c (C) y = x + 1/2 cos 2 (x + y) – c (D) None of these

Q.62

Q.63

dy = sin (x + y) + cos (x + y) is-

The solution of dx

(D) None of these

(C)

(B)

(A)

y  

y  

y  

log

log

log

1 tan

x

2

1 tan

1 tan

x

2

2

x

+ c = 0

=

=

x + c

x + c

dy = (4x + y + 1) 2 is-

The solution of dx

 (A) 4x – y + 1 = 2 tan (2x – 2c) (B) 4x – y – 1 = 2 tan (2x – 2c) (C) 4x + y + 1 = 2 tan (2x + 2c) (D) None of these

Question

based on

Differential Equation of homogeneous type Q.64

Q.65

Q.66

The solution of the differential equation

x 2 dx dy = x 2 + xy + y 2 is-

y

 (A) tan –1   x   (B) tan –1    y   x  (C) sin –1    y   x  (D) tan –1  x     y   

= log x + c

= – log x + c

= log x + c

= log x + c

The

solution

of

the

differential

dy = y (log y – log x + 1) is-

x dx

(A) y = xe cx

(C)

y + e x = 0

(B) y + xe cx = 0 (D) None of these

The solution of the equation dx dy =

x

y

x

y

c (x 2 + y 2 ) 1/2 +

(B) c (x 2 + y 2 ) 1/2 =

(C)

(D) None of these

(A)

=

e

e

e

tan

tan

1

(y / x)

(y / x)

tan

1

(y / x)

1

c (x 2 – y 2 )

equation

is-

 Q.67 The solution of the differential equation (x 2 + y 2 )dx = 2 xy dy is- (A) x = c (x 2 + y 2 ) (B) x = c (x 2 – y 2 ) (C) x + c (x 2 + y 2 ) = 0 (D) None of these Q.68 The solution of the equation x dy = y – x tan dx  y    x   is- (A) x sin  x     y    + c = 0 (B) x sin y + c = 0 (C) x sin  y   x    = c (D) None of these Question Linear Differential Equation based on Q.69 The solution of the differential equation, dy + y = x 2 is- dx x (A) 4xy = x 4 + c (B) xy = x 4 + c (C) 1 4 xy = x 4 + c (D) xy = 4x 4 + c Q.70 The solution of the differential equation dy + y = cos x is- dx 1 (A) y = 2 (cos x + sin x) + ce – x 1 (B) y = 2 (cos x – sin x) + ce – x (C) y = cos x + sin x + ce –x (D) None of these Q.71 The solution of the differential equation x dy + y = 2 log x is- log x dx
 (A) y = log x + c (B) y = log x 2 + c (C) y log x = (log x) 2 + c (D) y = x log x + c

Q.72

Q.73

Q.74

Q.75

Q.76

The solution of the equation

 x dy dx + 3y = x is- 4 (A) x 3 y + x + c = 0 4 4 (B) x 3 y = x + c 4 4 (C) x 3 y + x = 0 4 (D) None of these The solution of the differential equation

dy + y cot x = 2 cos x is-

dx

 (A) y sin x + cos 2x = 2c (B) 2 y sin x + cos x = c (C) y sin x + cos x = c (D) 2y sin x + cos 2x = c

The solution of (1 + y 2 ) dx = (tan 1 y – x) dy is -

(A)

(B)

(C)

(D) None of these

tan

1

y

=

e

tan

1

y

(tan 1 y – 1) + c

xe

xe

xe

tan

1

tan

1

y

y

= (tan 1 y + 1) – c

= (tan 1 y – 1) + c

The integrating factor of the differential equation

dy + y = 2 log x is-

(x log x) dx

(A)

(C)

log x

e x

(B) log (log x)

(D) x

The equation of the curve passing through the origin and satisfying the differential equation

(1 + x 2 )

dy + 2xy = 4x 2 is- dx

 (A) (1 + x 2 )y = x 3 (B) 2 (1 + x 2 )y = 3x 3 (C) 3 (1 + x 2 )y = 4x 3 (D) None of these

Q.77

Q.78

Q.79

The

solution

of

the

x

dy + y = x 2 + 3x + 2 is- dx

differential

(A)

(B)

(C)

xy =

xy =

xy =

x 3

3 x 2 + 2x + c

2

3

x

4

+

+ x 3 + x 2 + c

4

x

4

4

+

x 3

3

+ x 2 + c

equation

(D)

xy =

x

4

4

+

x 3 + x 2 + cx

dy =

1

The solution of the equation dx

x

 

y

1

 (A) x = ce y – y – 2 (B) y = x + ce y – 2 (C) x + ce y – y –2 = 0 (D) None of these

is-

Integrating

factor

of

the

dy + y tan x – sec x = 0 is-

dx

differential

(A) e sin x

1

(B) sin x

(C)

1

cos x

(D) e cos x

equation

 Question Equation reducible to linear form based on

Q.80

The solution of differential equation

dy + 1 = e xy is-

dx

(A) e y = e x / 2 + ce x

(B) e y = e x + ce x

(C) 3e y = e x / 2 + ce x

(D) None of these

LEVEL- 2

Q.1

Q.2

Q.3

Q.4

The order of the differential equation whose general solution is given by y = (C 1 + C 2 ) cos

5 , where C 1 , C 2 ,C 3 , C 4 , C 5 are

arbitrary constants, is-

(x + C 3 ) – C 4 .

e

x

C

 (A) 5 (B) 4 (C) 3 (D) 2

The differential equation of all circles in the first quadrant which touch the coordinate axes is of

order-

(A) 1

(C) 3

(B) 2

(D) None of these

The differential equations of all circles passing through origin and having their centres on the x-axis is

(A) dx dy =

y

2

x

2

2 x y

(C)

d

2

y =

y

2

x

2

dx

2

2 xy

(B)

(D)

dy =

y

2

x

2

dx

dy =

y

2

2

x

x

2

dx

2

xy

The solution of the equation

dy + y tan x = x m cos x is-

dx

 (A) (m+1) y = x m+1 cos x + c (m+1) cos x (B) my = (x m + c) cos x (C) y = (x m+1 + c) cos x (D) None of these

Q.5

Q.6

The

(sin x + cos x) dy + (cos x – sin x)dx = 0 is-

solution

of

the

differential

equation

 (A) e x (sin x + cos x) + c = 0 (B) e y (sin x + cos x) = c (C) e y (cos x – sin x) = c (D) e y (sin x – cos x) = c

The solution of the differential equation

 dy 3x 2 sin 2 x + 3 y = is - dx 1